2024
DOI: 10.3390/su16020511
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Using Different Types of Compost on the Growth and Yield of Corn

Anita Zapałowska,
Wacław Jarecki

Abstract: The cultivation of corn holds immense importance as a foundational global grain crop, catering to human sustenance and serving as vital animal feed. Moreover, corn plays a substantial role in biofuel production. Additionally, cultivating corn can have a positive effect on crop rotation by improving soil quality and reducing erosion. In a pot trial using six distinct compost variations derived from different organic wastes as fertilizers for GS210 corn, specific indices, such as Fv/Fm (0.80, 0.80, 0.81), Fv/F0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…The present results agree with those obtained by (Nofal & Silem, 2003) who found that FYM application did not significantly affected this trait. On the other hand, (Kandil et al, 2020;Zapałowska & Jarecki, 2024) obtained significant increase in number of grains/ear due to application of animal manures.…”
Section: Number Of Grains/rowmentioning
confidence: 97%
“…The present results agree with those obtained by (Nofal & Silem, 2003) who found that FYM application did not significantly affected this trait. On the other hand, (Kandil et al, 2020;Zapałowska & Jarecki, 2024) obtained significant increase in number of grains/ear due to application of animal manures.…”
Section: Number Of Grains/rowmentioning
confidence: 97%
“…The research gap of the by Zapałowska and Jarecki (2024) is that there is a lack of information on the specific effects of different types of compost on corn growth and yield. While there are studies on the effects of compost on other plants and soils, there is a need for research focused on corn specifically.…”
Section: Introductionmentioning
confidence: 99%